(untitled) (Nonlinear Studies, 2025)
The ψ-Hilfer fractional integro-differential equation sensitive to instantaneous impulses is studied in this research. Establishing the presence and uniqueness of its solution is the main objective. In particular, the existence of a unique solution is investigated using the fixed point theorems, Banach’s and Krasnoselskii’s. An example is provided to demonstrate the obtained outcome.